2016
DOI: 10.1007/s11164-016-2482-2
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characteristics of municipal thickened excess activated sludge (TEAS): impacts of pH, temperature, solid concentration and polymer dose

Abstract: Rheological characterization of sludge is known to be an essential tool to optimize flow, mixing and other process parameters in wastewater treatment plants. This study deals with the characterization of thickened excess activated sludge in comparison to raw primary sludge and excess activated sludge. The effects of key parameters (total solid concentration, temperature, and pH) on the rheology and flow behaviour of thickened excess activated sludge were studied. The rheological investigations were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…These changes directly influence the rheological properties of digested sludge during dewatering (Sanin 2002). Viscosity generally lowers with higher temperature and shear rate, and a similar trend was reported by many researchers (Farno et al 2013;Eshtiaghi et al 2013;Hasar et al 2004;Yeneneh 2014;Hong et al 2015Hong et al , 2016.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…These changes directly influence the rheological properties of digested sludge during dewatering (Sanin 2002). Viscosity generally lowers with higher temperature and shear rate, and a similar trend was reported by many researchers (Farno et al 2013;Eshtiaghi et al 2013;Hasar et al 2004;Yeneneh 2014;Hong et al 2015Hong et al , 2016.…”
Section: Introductionsupporting
confidence: 71%
“…Rheological and fluid dynamic characteristics of sludge are also essential in the design and operation of processes in wastewater treatment plants due to their influence on heat and mass transfer and mixing (Baroutian et al 2013;Bandrés et al 2009). The rheological characteristics of digested sludge depend on many factors such as source, solid concentration, temperature, and sludge treatment method (Ratkovich et al 2013;Abu-Jdayil et al 2010;Hong et al 2015Hong et al , 2016. Total solid concentration is one of the major factors that affect the rheology and flow behavio of digested sludge.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the gradual decrease in the removal efficiency of the COD from 95% to 45% in noninoculated bioreactor exposed to the leachate resulted in the formation of very poor-quality effluent with a quality index of 250 and strongly alkaline pH. The pH of wastewater is considered to be among the most critical factors for the stable operation of sewage plants because it affects the strength and surface charge of the sludge flocs [45]. It can be concluded that the bioaugmentation of the AS with Pseudomonas strains made it possible to maintain the system stability because these bacteria positively affected the microbial biodegradation of the contaminants in the sewage and thus helped to maintain stable pH conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate pH is a crucial factor for the stable operation of a sewage plant because it affects the strength and surface charge of the AS flocs [63]. Extreme pH conditions can lead to an inhibition of the growth of the AS microorganisms [64].…”
Section: Discussionmentioning
confidence: 99%